Deskripsi Perbedaan Pengetahuan Dasar Matematika Siswa Kelas VII SMP Negeri dan SMP Swasta Di Kota Kendari Tahun Pelajaran 2016/2017 - Faad Maonde; Anwar Bey; Adawia . (Jurnal Pendidikan Matematika, 2016)
This research is a quantitative descriptive research that aims to know the basic knowledge of mathematics students of Public Junior High School and students of private Junior High School class VII at the material operations of integers and fractions. This research  population was all students of class VII students of Public Junior High School and students of private Junior High School in Kendari with a sample of 162 students. The sampling technique using stratified random sampling and cluster random sampling. The data collection techniques in this study uses the test method. The results showed that the basic knowledge of mathematics students of class VII of  Public Junior High School and Private Junior High School in Kendari city that are in the low category were Y <60. A basic knowledge of mathematics students of Public Junior High School higher than students of private junior high school with an average value of 44.57 for Public Junior High School students and 38.41 for private junior high school students . The highest average value of Public Junior High School students was 57.11 and the average value of the ultimate private junior high school students was 47.68.